Effect of Pulse Width Modulation on Proportional, Integral, and Derivative Coefficient Characteristics - Suhendra, Tonny (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
Based on the value of feedback obtained from the sensor (LDR), the PID algorithm uses the error value obtained from the comparison between the sensor value and the setpoint value to perform calculations so that the PWM generator will use the output value to produce a row of pulses that will be converted to a voltage (signal) with a range of 0 to 255 (0 volt to 5 volt) and is used to turn on the LED lamp according to the desired light level. The output characteristics generated by the PID control for each coefficient can be used as a benchmark to determine the correct coefficient value for Propotional coefficient, Integral coefficient and Derivative coefficient as a whole. From the test results, it can be seen that the coefficient value adjustment can be taken based on the size of the difference or error contained in the system. If the difference in error is slight, the use of large coefficient values, especially in derivative coefficients. It helps the system achieve a stable condition and reduces overshoot. Still, if the error value is significant, then applying a considerable efficiency value will make the system achieve stable condition stable becomes a little tricky because it is possible to overshoot the PID output.